Concussion in para sport - Kissick, J.; Webborn, N. (Physical Medicine & Rehabilitation Clinics of North America, 2018)
Although Para athletes (the International Paralympic Committee term for sportspeople with a disability) are exposed to a risk of concussion just like their able-bodied counterparts, there has been little research into the incidence of concussion in para sport. Existing assessment and management guidelines and tools have been developed for the general sport population but may not be appropriate for use in some para-athletes. This review examines what is currently known about concussion in para sport and identifies challenges and opportunities in moving knowledge on this topic forward.